2014
DOI: 10.1503/cjs.003913
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes of minimally invasive endoscopic and conventional sternotomy approaches for atrial septal defect repair

Abstract: Background:Although ischemic stroke is a well-known complication of cardiovascular surgery it has not been extensively studied in patients undergoing noncardiac surgery. The aim of this study was to assess the predictors and outcomes of perioperative acute ischemic stroke (PAIS) in patients undergoing noncardiothoracic, nonvascular surgery (NCS). Methods:We prospectively evaluated patients undergoing NCS and enrolled patients older than 18 years who underwent an elective, non-daytime, open surgical procedure. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 35 publications
0
14
0
Order By: Relevance
“…Stroke presenting immediately after extubation is rare and suggests intraoperative etiology. Bitekar et al found that age and preoperative history of stroke were strong risk factors for peri-operative acute ischemic stroke in patients undergoing non-cardiaothoracic, non-vascular surgery [12]. Thus if a previous episode of stroke is not disclosed, it can alter the course of intra-operative and post-operative events.…”
Section: Discussionmentioning
confidence: 99%
“…Stroke presenting immediately after extubation is rare and suggests intraoperative etiology. Bitekar et al found that age and preoperative history of stroke were strong risk factors for peri-operative acute ischemic stroke in patients undergoing non-cardiaothoracic, non-vascular surgery [12]. Thus if a previous episode of stroke is not disclosed, it can alter the course of intra-operative and post-operative events.…”
Section: Discussionmentioning
confidence: 99%
“…These unmodifiable factors include increasing age and female gender (5,8,9,12,24,31,32). Other independent risk factors include previous history of stroke or TIA, renal failure, diabetes mellitus, atrial fibrillation, congestive heart failure, smoking status, emergency surgery, and cardiac valvular disease (5,8,9,12,24,31).…”
Section: Risk Factors and Risk Optimizationmentioning
confidence: 99%
“…Besides the neurological deficit experienced by an individual after stroke, perioperative stroke is associated with longer hospital stays and higher disability, discharge to long term care facilities, and risk of mortality (2,5,7,8). Perioperative stroke also is associated with much higher mortality (26%-87% ) (10) as compared with stroke mortality in the non-perioperative setting (16%-23%) (10)(11)(12).…”
mentioning
confidence: 99%
“…The reported incidence of perioperative stroke in non-cardiac surgery ranges from 0.1-4.4%, which may be an underestimation as minor strokes and TIAs are likely to be under-reported. [5][6][7][8][9][10][11][12][13][14] The most consistently reported independent predictor for perioperative stroke is a previous stroke and, therefore, the perioperative management of this cohort of patients needs to be carefully tailored to minimise risk. 15,16 In addition, perioperative withdrawal of antiplatelets or anticoagulants and postoperative immobility can aggravate a surgeryinduced hypercoagulable state thus increasing the risk of a perioperative cerebral thrombotic event.…”
Section: Introductionmentioning
confidence: 99%
“…Perioperative stroke has been strongly associated with poor outcomes: increased rates of postoperative respiratory and cardiac complications, increased length of stay, greater rates of institutionalisation and increased mortality. [12][13][14][15][16] Mortality rates associated with stroke following non-cardiac surgery are reported in the range of 18-32% [12][13][14] and are even higher in those with a previous history of stroke. 8 This review aims to provide a practical, evidence-based approach to the management of patients with a history of stroke or TIA undergoing elective non-cardiac, non-carotid surgery.…”
Section: Introductionmentioning
confidence: 99%